Trends in Gender-Affirming Surgeries in the United States from 2010 to 2021 - Ha, Ally; Garoosi, Kassra; Hale, Elijah; Higuchi, Ty; Winocour, Julian; Mathes, David W.; Kaoutzanis, Christodoulos (Indian Journal of Plastic Surgery, 2024)
Introduction: In 2017, an estimated 1.6 million adults and 150,000 teenagers identified as transgender in the United States. With ever-changing legislative developments regarding health care benefits for this population and the increasing number of patients presenting for gender-affirming surgery (GAS), there is a scarcity of literature on the temporal trends within the past decade. The objective of this study was to examine the temporal trends of the utilization of GAS.Methods: We conducted a cross-sectional study using TriNetX, a federated research network containing deidentified aggregate patient data. Using International Code of Disease (ICD) and Current Procedural Terminology (CPT) codes, we identified patients with a diagnosis of gender dysphoria who underwent GAS from 2010 to 2021. Basic demographic information and complications were analyzed. Complications of interest included site failure, infection, and systemic complications.Results: We identified a total of 8,403 patients who underwent GAS between January 2010 and December 2021. The number of procedures per year increased nearly 500% between 2016 and 2021 from 421 procedures to 2,224 procedures. Our demographic results were consistent with previous survey-based studies. The average age of patients who underwent masculinizing surgeries was consistently younger than those who underwent feminizing surgeries. Most patients undergoing GAS were of white race. The overall complication rate was 4.7%.Conclusion: In conclusion, our study reveals a significant and rapid rise in the utilization of GAS in the United States, with a fivefold increase in procedures between 2016 and 2021. The demographic characteristics and low complication rates observed highlight the evolving landscape of health care for transgender individuals and the need for ongoing assessment and support in this field.
Keywords: gender-affirming surgery; gender reassignment surgery; surgical outcomes; transgender surgery; TriNetX